Molecular modelling comparisons, optical and band gap characterisation of 4-sulfocalix[4]arene thin film - Farish Armani Hamidon,; Faridah Lisa Supian,; Mazlina Mat Darus,; Wong, Yeong Yi; Nur Farah Nadia Abd Karim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The advantageous property of water-soluble calixarenes is their ability to form stable complexes with inorganic guest molecules. Due to these attributes, their application in areas including molecular recognition, sensing, and supramolecular chemistry is extraordinarily alluring. The 4-sulfocalix[4]arene (SC[4]) is a water-soluble molecule and a derivative of the calixarene family that has both aromatic rings and sulfonate groups. The thin films were prepared using a spin-coating technique and characterised by Ultraviolet-Visible Spectroscopy (UV-Vis). By employing the Corey-Pauling-Koltun (CPK) model in conjunction with density functional theory (DFT), the height and diameter of SC[4] were precisely determined by devotedly representing its molecular shape and size. Then, the calixarene thin film’s optical properties and light absorption by the thin film were determined using the absorbance graph and Beer-Lambert law equation. The band gap energy of the thin film was determined to be equal to 4.44 eV through the Tauc-plot method. These results substantiate the integration of CPK models validated using DFT for measuring the size of SC[4] molecules and characterising the thin film’s optical characteristics. In a nutshell, the implementation of the CPK models was validated with DFT to determine the height and diameter of the SC[4] and the optical characterisation of its thin film was thoroughly determined in this study. The results obtained from this study are not only essential for understanding the properties of SC[4] but also inspire further research for multiple applications such as molecular recognition, adsorption and supramolecular chemistry.